Prevalence of prediabetes and undiagnosed diabetes in a large urban middle-aged population: the CARVAR 92 cohort - Marie Hauguel-Moreau; Hélène Hergault; Laure Cazabat; Marion Pépin; Alain Beauchet; Vincent Aïdan; Mounir Ouadahi; Loïc Josseran; Mirella Hage; Christophe Rodon; Olivier Dubourg; Ziad Massy; et al. (Cardiovascular Diabetology, 2023)
Abstract Background The aim of this study was to assess the prevalence of prediabetes and unknown diabetes and its long-term change in a large middle-aged urban population. Methods We conducted a screening campaign between 2007 and 2018 for cardiovascular risk factors in the western suburbs of Paris including subjects aged 40–70 (CARVAR 92). Among subjects who reported no previous diabetes, prediabetes and undiagnosed diabetes were defined as follows: fasting plasma glucose (FPG) ≥ 6.1 mmol/l (110 mg/dl) and < 7 mmol/l (126 mg/dl) for prediabetes according to WHO criteria (FPG between 5.6 and 6.9 mmol/l according to ADA criteria) and FPG ≥ 7.0 mmol/l for undiagnosed diabetes. Results Of the 32,721 subjects in the CARVAR 92 cohort, 32,675 were included in this analysis. The median age of the patients was 56 years [30, 94], 45.4% were male, 5.9% had known diabetes, 36.4% were overweight and 18.7% obese. Among patients without previously known diabetes (n = 30,759), 8.1% had prediabetes according to WHO criteria (27.2% according to ADA criteria) and 2.3% had diabetes. Subjects with prediabetes and unknown diabetes were more likely to be male, older, and overweight or obese than non-diabetic subjects. From 2007 to 2018, the prevalence of prediabetes, unknown diabetes, and known diabetes decreased, except for prediabetes which remained stable for people aged 55–64. Conclusion The prevalence of prediabetes and unknown diabetes remains high but decreased during a 12-year period. About one-quarter of diabetes cases remain undiagnosed. Our results highlight that there is still a room for screening and cardiovascular prevention campaigns. Trial registration: IRB00012437.